PENGGUNAAN BAHASA GAUL DI KALANGAN REMAJA DAN DAMPAKNYA TERHADAP BAHASA INDONESIA - Amelia Oktaviarta Simangunsong; Ottolinda Martha Tebay; Munaya Syakila; Harlen S.M Pasaribu; Syafira; Marsel Josua Pasaribu; Ita Khairani (STKIP Subang, 2026)
The rise of social media has made the use of slang among teenagers increasingly common in everyday life. Slang is typically used when communicating with peers because it is considered more casual and easier to understand. However, the overuse of slang is also beginning to affect the proper use of Indonesian, particularly in formal situations. This study aims to examine the use of slang among teenagers and its impact on the use of Indonesian. This study employs a qualitative descriptive method, utilizing data collection through a survey distributed via Google Forms to 37 respondents aged 15–23 years, supplemented by a literature review from various scientific journals. The results indicate that the majority of teenagers use slang in daily communication because it is perceived as more comfortable within social circles. In addition to having a positive impact in the form of more intimate and relaxed communication, the use of slang also causes some adolescents to become accustomed to using non-standard language in formal and academic settings. So, language use needs to be adapted to the situation and context so that the Indonesian language remains preserved as a national identity.